Group-Inclusion for Students with Special Educational Needs in Mainstream Schools - Yael Tsafrir; Mușata Bocoș (Babes-Bolyai University, 2023)
Inclusion of students with special educational needs (SEN) in mainstream schools and mainstream classes is a global mission. Together with cases of success in including students with SEN in the mainstream structures, various studies highlight a lot of criticism concerning policy and implications. The failure of inclusion is reflected both in academic achievements and well-being of the students with SEN. It also affects families and is of great concern to stakeholders, principals, and educational staff as well. The present article emphasizes Group-inclusion as a social intervention for improving educational inclusion. The authors describe principles of Positive Psychology Theory and positive education, as well as principles of the Generative Interactions Theory, as the basis for successful Group-inclusion, which may contribute to the social involvement of students with SEN with their peers. Description of Group-inclusion and examples of implementation are given, and the advantages and costs of Group-inclusion are discussed. Through Group-inclusion the social feelings and attitude of students with SEN in mainstream schools can be improved, as well as their subjective well-being.